(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This paper aims an approach to some of the most solid assumptions of Literary Theory considering the critique of Michel Foucault and, in lesser extent, that of Roland Barthes and Jacques Derrida. Some of those assumptions include literary criticism in its traditional way, the role of the authorship in literature and the literature itself as an institutional device set up to claim upon the value of the literary discourses. In order to develop Foucault’s arguments, we undertake a reading of some “minor writings” corresponding to “the first Foucault” in the sixties’ decade –keynotes, interviews, journal articles and so on– although we are mostly based on two or three unpublished documents on literature topics from the Michel Foucault Archives located at the Institut Mémoires de l’Édition Contemporaine, in Caen, France.